Factors influencing enrolled nursing students' academic performance at a selected private nursing education institution in KwaZulu-Natal - Makhosazane B. Dube; Puseletso R. Mlotshwa (AOSIS, 2018)
Background: The success of any educational institution is measured by its academic performance or how well students meet the standards set out. Currently, nursing students' academic failure is a phenomenon of growing international interest because of its economic impact and its negative effects on the availability of future nurses in different health care systems. Factors identified as influencing the academic performance of students include the socio-economic background of parents or guardians, lecturer-student relationships, academic support services, demographic factors, quality of nurse educators, availability of facilities in the school, the language of instruction and level of entry qualifications of students. Objectives: The purpose of this study was to describe the perceptions of enrolled student nurses on factors influencing their academic performance in a private nursing school in KwaZulu-Natal, South Africa. Method: Data were collected from 100 respondents using an adapted instrument related to the factors believed to influence students' academic performance. Results: The results showed that parental involvement in education, good and supportive relationships between nurse educators and students, classroom computer technological gadgets, internet connection and adequate learning facilities were perceived as fostering better academic performance of students. In contrast, poor family background, use of English language for classroom instruction as well as negative peer group influences were leading to poor academic performance. Conclusion: Nursing institutions should, therefore, select students with higher-level entry qualifications, early identify at-risk students, recruit more qualified nurse educators and upgrade their facilities.